Trends in the world aluminum industry - Brubaker, Sterling (Johns Hopkins Press, 1967)
This book introduce the trends of aluminum consumption and production. Future demand for aluminum, basic technology of the aluminum industry. Structure of the international industry, trade and trade policies, elements of the cost structure of the industry...